Much ado about nothing. - Phillips, Owen.; Shakespeare, William, 1564-1616.; Barter Theatre (Organization : Abingdon, Va.) (1946)
The Barter Theater of Virginia presents its 1946-47 season: "Blithe Spirit," by Noel Coward, staged by Owen Phillips, "Much Ado About Nothing," by William Shakespeare, staged by Owen Phillips.
Barter Theatre, 1946-47.
Cast: Gordon Sommers, Jim Cameron, Chaucy Horsley, Joan DeWeese, Elizabeth Wilson, Mary Hayden, Margaret Thomson, Boyd Seghers, Bela Negie, Robert Pastene, Woodrow Romoff, Tom McDermott, Herbert Nelson, John Vivyan, Karl Lukas, George Burns, Mell Turner, Jerry Uchin, Mary Louse Howard, Betty Gooch, Ted Montague, Martin Waldron, Sally Chamberlin, Jo Waffle, Barbara Gillespie, Larry Gates, Frederic Warriner, Karl Lukas, Hank Colman, Ernest Borgnine.
Title devised by Library staff.
With: Blithe spirit / Noel Coward. Issued together.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Virginia -- Abingdon; Theater programs -- 1946.